An Adrenocortical Carcinoma Associated with Non-Islet Cell Tumor Hypoglycemia and Aberrant ACTH Production - M. D. S. A. Dilrukshi; A. W. Wickramarachchi; D. D. K. Abeyaratne; Brian Shine; Bahram Jafar-Mohammadi; N. P. Somasundaram (Case Reports in Endocrinology)
Introduction. Adrenocortical carcinomas (ACCs) are infrequently reported to present with severe hypoglycemia syndrome resulting from the secretion of insulin-like growth factor II (IGF-II) by tumor cells. Adrenocorticotropic hormone- (ACTH) independent hypercortisolism is the norm of hormonally active ACCs, but aberrant ACTH production by tumor cells can theoretically cause ACTH-dependent hypercortisolism. The purpose of this report was to present a case of an ACC manifested with the co-occurrence of two extremely rare presentations. Case Description. We present a rare case of a 43-year-old male patient admitted with recurrent episodes of severe non-ketotic and non-insulin-mediated hypoglycemia due to IGF-II mediated disease and ACTH-dependent Cushing’s syndrome. He was diagnosed with a diffusely disseminated adrenocortical carcinoma with immunohistochemistry of tumor cells showing focal ACTH immunostain positivity. Conclusion. Non-islet cell tumor hypoglycemia and ACTH-dependent Cushing’s syndrome are extremely rare presentations of an ACC, and co-occurrence of these entities in a single patient is never reported in the literature.